MEMBACA A-QUR'AN DENGAN TRANSLITERASI ARAB LATIN: - Syatri, Jonni (SUHUF, 2018)
This article discusses the phenomenon of the use of transliteration in reading the Qur’an. The focus of the research takes place in Payakumbuh and its surroundings which is known as an area whose people are predominantly muslim. This research was conducted by using a qualitative approach. Data are obtained by structured interviews and observations. In this study it can be seen that there are some people who use transliteration in reading the Qur’an. They hope that the Qur’anic transliteration can be continually developed in order to make it easier for those who are unable to read the Qur’an in Arabic letters. However, some groups, such as teachers and religious educators, do not approve the transliteration of the Qur’an.According to them, the transliteration of the Qur’an has a greater harm than that of the benefits. The existence of transliteration is worried to weaken the enthusiasm of muslims to learn how to read the Koran in Arabic letters. In addition to that, the Latin letter symbol is considered unable to accurately represent Arabic letters in terms of makhraj and its nature, so it is worried that there will be a mispronunciation of therecitation of the Qur’an. KeywordsReading the Qur’an, Latin-Arabic transliteration, learning Al-Qur’an, reading and writing the Qur’an.